(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2019)
State enactments are sets of laws enacted and passed at the State Legislative Assembly (Dewan Undangan Negeri, DUN) in Malaysia. This article intends to analyze the offences and punishments that relate to zakat (poor tax) based on state enactments. This article begins by briefly describing the administration and management of zakat in Malaysia. Next, the literature review scans the sources of written law beginning with the constitution, enactments and subsidiary laws as well as the legal study of zakat in Malaysia. As legal research, this article is qualitative in nature and employs the historical and comparative approaches. The analysis involves descriptive techniques such as tables and charts, as well as ratio and proportion analysis. In comparing state criminal offence enactments, the findings of the study show that there is a difference in offences and punishment in Malaysia. Keywords: zakat, enactments, State Islamic Religious Council, Islamic law